Estimation of Exopolysaccharides (EPS) Producing Ability of Cr (VI) Resistant Bacterial Strains from Tannery Effluent - Rida Batool; Usama Marghoob; Asma Kalsoom (Journal of Basic & Applied Sciences, 2017)
Chromium is a known heavy metal and recognized as a carcinogen to the biological systems. Previously isolated Cr (VI) resistant Exiguobacterium UE1 and UE4 were used in this study. These strains were analysed for exopolysaccharides (EPS) production for the remediation of Cr (VI) contaminated soils. Both the strains could tolerate about 250µg/ml of Cr (VI) stress. Strain UE1 showed 100% Cr (VI) removal whereas UE4 reduced 99.2% at an initial concentration of K2CrO4 100µgml-1. Optimum growth was observed at 37ºC and pH 7 for both strains. Strains exhibited significant EPS production under Cr (VI) stress and non-stress conditions. However, UE1 showed increased production of released as well as loosely bound EPS (0.36g/100ml and 0.152g/100ml respectively) under Cr (VI) supplemented condition. Thin Layer Chromatography (TLC) technique confirmed the presence of sugars in EPS samples after hydrolysis. Fourier Transforms Infrared Spectroscopy (FTIR) analysis showed the involvement of various functional groups such as hydroxyl group and aromatic compounds in the binding of Cr (VI) ions to the EPS. These findings suggest that strains UE1 and UE4 isolated from local tanneries of Pakistan can be used for remediation of Cr (VI) pollutes soils.